The Influencer of Customer Experience on Interest to Revisit Through Satisfaction with Visiting Segunung Traditional Village of Segunung Wonosalam Jombang - Fahimah, Mar'atul; Wulandari, Niken (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This research was conducted to identify whether or not there is an influence that occurs between customer experience on return visit interest through visiting satisfaction in the Segunung Traditional Village tour Wonosalam Jombang Research Methods: This study uses an associative method with a quantitative approach. The population in this study were tourists who had visited Segunung Traditional Village. To obtain data in accordance with this study, researchers used a questionnaire as a medium in collecting data and used purposive sampling techniques in determining respondents. Respondents in this study were 100 respondents. This study uses SEM PLS (Structural Equation Modeling based on Partial Least Square) analysis technique by analyzing the outer model, inner model and hypothesis testing. Results and discussion: The results in this study are variable customer experience on interest in visiting again through visiting satisfaction has a positive but insignificant effect. Implication: The results of this study imply that in order to increase visitors' interest in returning, managers need to consistently create a positive customer experience. A good experience will increase visitor satisfaction, which ultimately encourages their desire to make repeat visits. Therefore, strategies to improve the quality of service, facilities, and interaction with customers are important factors that must be considered and developed sustainably.